Análise cromossômica por microarranjo aplicada ao diagnóstico das síndromes genômicas que envolvem a região 22q11.2 - Cunha, Ana Julia da (2016)
The chromosome 22q11.2 region has long been implicated in genomic diseases. Some genomic regions exhibit numerous low copy repeat with high identity in which provide increased genomic instability and mediate deletions and duplications in many disorders. DiGeorge Syndrome is the most common deletion syndrome and reciprocal duplications could be occurring in a half of the frequency of microdeletions. We described five patients with phenotypic variability that carries deletions or reciprocal duplications at 22q11.2 detected by Chromosomal Microarray Analysis. The CytoScan HD technology was used to detect changes in the genome copy number variation of patients who had clinical indication to global development delay and a normal karyotype. We observed in our study three microdeletions and two microduplications in 22q11.2 region with variable intervals contained known genes and unstudied transcripts as well as the LCRs that are often flanking and within this genomic rearrangement. The identification of these variant are of particular interest due to it may provide insight in genes or genomic regions there are crucial for specific phenotypic manifestations and are useful to assist the quest for understanding the mechanisms subjacent to genomic deletions and duplications.